2021
DOI: 10.3390/antibiotics10020204
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Small Molecules as Antibacterials: Non-Cytotoxic Diarylureas Analogues of Triclocarban

Abstract: Triclocarban (TCC), a broad-spectrum lipophilic antimicrobial agent, is a diarylurea derivative that has been used for more than 60 years as a major ingredient of toys, clothing, food packaging materials, food industry floors, medical supplies and especially of personal care products, such as soaps, toothpaste and shampoo. In September 2016, the U.S. FDA banned nineteen antimicrobial ingredients, including TCC, in over-the-counter consumer antiseptic wash products, due to their toxicity. Withdrawal of TCC has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Incorporating such chemical elements into hand hygiene products can substantially increase the extent of human exposure to them and can cause unexpected health risks. Moreover, the intentional or unintentional disposal release of these chemical elements contaminates the environment ( Catalano et al, 2021 ). As a cross-sectional study, Alhazmi et al reported that 34.8% of the participants used antibacterial soap against the coronavirus ( Alhazmi et al, 2019 ).…”
Section: A Sustainable Solution: Biodegradable Hand Soapmentioning
confidence: 99%
“…Incorporating such chemical elements into hand hygiene products can substantially increase the extent of human exposure to them and can cause unexpected health risks. Moreover, the intentional or unintentional disposal release of these chemical elements contaminates the environment ( Catalano et al, 2021 ). As a cross-sectional study, Alhazmi et al reported that 34.8% of the participants used antibacterial soap against the coronavirus ( Alhazmi et al, 2019 ).…”
Section: A Sustainable Solution: Biodegradable Hand Soapmentioning
confidence: 99%
“…The compounds 3 and 4 described by Sarveswari et al (2018) [ 112 ] showed the same activity of the standard (ciprofloxacin) against the Gram-negative Proteus mirabilis (ATCC 19181) (zone of inhibition of 23 and 24 mm, respectively, at a concentration of 200 µg/mL compared to 30 mm of ciprofloxacin). Catalano et al (2021) [ 71 ] described the properties of a series of diarylureas analogues of TCC: six compounds ( 5 – 10 ) showed the same activity of TCC against S. aureus (MIC = 16 µg/mL). Out of the six, particularly interesting were the compounds 5 and 6 that also demonstrated even higher activity than TCC against E. faecalis (MIC = 32 µg/mL versus MIC = 64 µg/mL of TCC).…”
Section: Analogues Of Tccmentioning
confidence: 99%
“…Recently, Pujol et al (2018) [70] determined the MIC value for TCC against Staphylococcus aureus ATCC 12600 (MIC = 0.5 µg/mL) and found that it was the same as ciprofloxacin. In a successive paper, the MIC value for TCC was 16 µg/mL against S. aureus ATCC 29213 and 6538P (versus 0.5-2 µg/mL of norfloxacin) [71]. Although TCC has been widely used as an antimicrobial for over 50 years, it was only recently that concerns were raised about its endocrine disruptive properties.…”
Section: Biological Activity Of Tccmentioning
confidence: 99%
“…Again, Catalano et al [24] reviewed the different properties of diarylureas [8,25], namely ureas bearing two aromatic moieties as substituents, focusing on their role as important pharmacophore in anticancer drugs over the past 10 years. A clinically used member of this class, sorafenib was the lead compound approved from Food and Drug Administration (FDA) and the European Medicinal Agency (EMEA) for the treatment of advanced metastatic hepatocellular carcinoma and advanced renal cell carcinoma, paving the way to other diarylureas derivatives, such as regorafenib, linifanib, tivozanib and ripretinib, which share the ability to inhibit the kinases.…”
Section: Contributionsmentioning
confidence: 99%